3D follow‐up study of facial asymmetry after developmental dysplasia of the hip. (4th July 2018) - Launonen, A.; Maikku, M.; Vuollo, V.; Pirttiniemi, P.; Valkama, A. M.; Heikkinen, T.; Kau, C. H.; Harila, V.
Structured Abstract: Objectives: To evaluate the change in facial asymmetry among subjects treated for developmental dysplasia of the hip (DDH) from childhood to adolescence. Setting and sample population: A total of 39 adolescents (26 females and 13 males), born and treated for DDH during 1997‐2001, participated in the first examination in 2007 (T1; at the age of 8.2) and in the follow‐up in 2016 (T2; at the age of 16.6). Material and methods: In this longitudinal study, three‐dimensional (3D) images were taken using a 3DMD face system based on a stereophotogrammetric method. Facial asymmetry was determined as the average distance (mm) calculated between the original and superimposed mirrored face and the symmetry percentage (%) calculated as the face area where the distance between the original face and the mirrored surface does not exceed 0.5 mm. Results: Results showed increased asymmetry from T1 to T2. The average distance increased for whole face (from 0.51 mm to 0.59 mm, P = .001), upper face (from 0.41 mm to 0.49 mm, P = .005), mid‐face (from 0.48 mm to 0.57, P = .002) and lower face (from 0.74 mm to 0.85 mm, P = .147). Facial symmetry percentage decreased for whole face from 61.23% to 55.38% ( P = .011), for upper face from 69.27% to 62.24% ( P = .005) and for mid‐face from 62.29% to 55.63% ( P = .007) and for lower face from 43.37% to 42.19% ( P = .66). Conclusion: Facial asymmetry increases from childhood to adulthood in subjects treated for DDH. Orthodontic treatment does not eliminate this asymmetric facial growth.